The Improvement of Tamm Interface State Detection by Using a Porous Layer between a Metal Nanostructured Grating and a DBR - Oumaima Haidar; Baptiste Mathmann; Yannick Dusch; Mohamed El Barghouti; Gaëtan Lévêque; Abdellatif Akjouj; Abdellah Mir; Abdelkrim Talbi (Proceedings)
In this work, we propose a sensor based on Tamm plasmonic resonance; the structure is composed of gold nanoribbons deposited on a Distributed Bragg Reflector (DBR) (SiO2/Si3N4)6. We have enhanced the sensitivity of our sensor from 40 nm/RIU to 200 nm/RIU for a refractive index change of 1% by replacing the last layer of Si3N4 in contact with gold with porous Si3N4 with a porosity of p = 40%.